Consumerism and consumerist lawsuits - Oliveira , Tamilys Madeiro de; Lacerda, Edmundo Vieira (Seven Editora, 2023)
This study aims to understand how consumerism affects consumer legal demands and analyze the importance of consumer law as a tool for protecting consumer interests. The problematization lies in the need to understand how legal demands related to consumption have been treated by the legal system and how judicial decisions have impacted consumer relations. The justification for this study lies in the importance of the topic for contemporary society, as well as in the relevance of consumer law as a means of protecting consumer interests. The methodology adopted for this literature review will consist of an exploratory research of relevant bibliographic sources, with critical and reflexive analysis of the concepts and arguments presented by selected authors. DOI:https://doi.org/10.56238/alookdevelopv1-158